Design science in operations management: conceptual foundations and literature analysis - Aline Dresch; Daniel Pacheco Lacerda; Paulo Augusto Cauchick-Miguel (Brazilian Journal of Operations & Production Management, 2019)
Goal: The aim of this paper is to show that design science and design science research may contribute as a methodological approach in the context of operations management.